Temperature-responsive culture surfaces for insect cell sheets to fabricate a bioactuator. (4th March 2019) - Uesugi, Kaoru; Sakuma, Yui; Akiyama, Yoshitake; Akiyama, Yoshikatsu; Iwabuchi, Kikuo; Okano, Teruo; Morishima, Keisuke
ABSTRACT: For the first time, we have fabricated insect-derived cell sheets by using temperature-responsive culture surfaces having a phase-transition temperature below 25°C. We prepared the temperature-responsive cell culture surfaces (tissue culture polystyrene, TCPS) by grafting a copolymeric gel consisting of hydrophobic N-tert-butylacrylamide (tBAAm) and N-isopropylacrylamide (IPAAm) units. First, to characterize the hydrophilic and hydrophobic properties of the copolymeric gel-grafted surfaces, static water contact angles of each surface were measured at various temperatures. By increasing the amount of tBAAm in the grafted copolymeric gel, the transition temperature of the gel was shifted to lower temperatures. At 25°C, the grafted copolymeric gel was dehydrated, and the insect-derived cells (AeAl2 cells) adhered on all the copolymeric gel-grafted surfaces. At 20°C, AeAl2 cells cannot adhere on the P(IPAAm-1.62tBAAm)-TCPS surface (the initial molar ratio of IPAAm and tBAAm (tBAAm = 1.62 mol%)) better than on other surfaces (TCPS and tBAAm = 4.88, 8.17 mol%). These two findings implied that the lower critical solution temperature of the copolymeric gel-grafted-TCPS existed from 20°C to 25°C. The laminin-coated P(IPAAm-1.62tBAAm)-TCPS surface showed temperature-dependent cell attachment and detachment properties, while AeAl2 cells were not detached from the extracellular matrix uncoated P(IPAAm-1.62tBAAm)-TCPS surface. AeAl2 cells and insect muscle cells were harvested as the respective sheets. GRAPHICAL ABSTRACT: